Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Profitabilitas (ROA) Pada BPRS HIK Bekasi Kantor Cabang Karawang - Nawawi, Ahmad; Nurdiansyah, Dian Hakip; Al Qodliyah, Diffah Sri Addafi (Falah: Jurnal Ekonomi Syariah, 2018)
The purpose of this study was to analyze the effect of mudharabah and musyarakah financing on profitability (ROA) at BPRS HIK Bekasi Karawang Branch Office. The research method using descriptive quantitative method with population is all quarterly financial statements of BPRS HIK Bekasi Karawang Branch Office. The results of the research conducted show that: (1) mudharabah financing has a positive and not significant effect on profitability BPRS HIK Bekasi Return on Assets (ROA) Karawang Branch Office 2009-2016 partially. This is evidenced by the sig value. 0.187> 0.05 and the value of t count is 1.351 <t table 2.042. (2) Musyarakah financing has significant negative effect on profitability BPRS HIK Bekasi Return on Assets (ROA) Branch Office Karawang 2009-2016 period partially. This is evidenced by sig. 0,000 <0,05 and the value of t count is -7,560> t table 2,042. (3) Mudharabah financing and musyarakah financing have a significant effect on profitability BPRS HIK Bekasi Return on Assets (ROA) Karawang Branch Office 2009-2016 period simultaneously. This is evidenced by the sig value. 0.000 <0.05 and the calculated f value is 31.022> f table 3.32.